Uplift and Expansion of the North Qilian Shan Recorded by Detrital Fission Tracks in the Jiudong Basin, NW China - Pan, Baotian; Zhao, Qiming; Hu, Xiaofei; Zhang, Jiaxin; Chen, Dianbao (Frontiers in Earth Science, 2022)
The North Qilian Shan, located in the northeastern front of the Tibetan Plateau, is an ideal region to study the expansion process of the plateau, while a clear expansion process is not revealed due to the lack of direct evidence and an accurate age control. In the Jiudong Basin (foreland basin of the north Qilian Shan), a continuous late Cenozoic sedimentary sequence and a reliable chronostratigraphic framework (post-7 Ma) provide us the material to study this process. In this study, we firstly analysis the provenance changes of the sediment by detrital apatite fission track (AFT) age distributions and apatite particle textures. The result shows that the first provenance change occurred 4.6-3.6 Ma, at when the sediment source from the southern part changed to the northern part of the North Qilian Shan, and it indicates that the North Qilian Shan Fault had propagated to its modern location. The second provenance change occurred at 3.0-2.4 Ma, at when the Yumu Shan and its south region began to provide sediments for the Jiudong Basin, and it indicates that the tectonic deformation had expanded to the North Yumu Shan Fault. Our finding suggests that two significant expansion events happened since the Pliocene for the North Qilian Shan.